Assessment of anxiety and self-esteem experienced by women during pregnancy - Nery, Nathália Gianini; Ribeiro, Patrícia Mônica; Leite, Eliana Peres Rocha Carvalho; Nogueira, Denismar Alves; Santos, Sérgio Valverde Marques dos; Terra, Fábio de Souza (Revista de Enfermagem da UFSM, 2021)
Objective: analyze the relationship between feelings of anxiety and levels of self-esteem experienced by women during pregnancy. Method: cross-sectional study carried out with 201 pregnant women in a city in the south of Minas Gerais, Brazil, between 2019 and 2020. For data collection, the questionnaire on sociodemographic characterization, lifestyle and information on pregnancy and important events in life was applied. Anxiety and Depression (anxiety subscale) and Rosenberg’s Self-Esteem Scale. For data analysis, descriptive and inferential statistics were used, through Pearson’s Chi-square, Fisher’s Exact and logistic regression tests. Results: the variables change in mood and the influence of physical change during pregnancy on women’s lives are associated with anxiety. As for self-esteem, no independent variable was statistically associated. Pregnant women with anxiety are three times more likely to have medium/low self-esteem. Conclusion: many women changed anxiety and self-esteem during pregnancy. Professional follow-up is important to monitor and prevent complications.